Proceedings of the 17th International Conference on New Trends in Fatigue and Fracture - Ambriz, Ricardo R.; Jaramillo, David; Plascencia, Gabriel; Nait Abdelaziz, Moussa (Springer International Publishing : Imprint: Springer, 2018)
This book presents the proceedings of one of the major conferences in fatigue, fracture and structural integrity (NT2F). The papers are organized and divided in five different themes: fatigue and fracture mechanics of structures and advanced materials; fatigue and fracture in pressure vessels and pipelines: mechanical behavior and structural integrity of welded, bonded and bolted joints; residual stress and environmental effects on the fatigue behavior; and simulation methods, analytical and computation models in fatigue and fracture.